2020
DOI: 10.3390/ma13204517
|View full text |Cite
|
Sign up to set email alerts
|

Microcomputed X-Ray Tomographic Imaging and Image Processing for Microstructural Characterization of Explosives

Abstract: Microstructural characterization of composite high explosives (HEs) has become increasingly important over the last several decades in association with the development of high fidelity mesoscale modeling and an improved understanding of ignition and detonation processes. HE microstructure influences not only typical material properties (e.g., thermal, mechanical) but also reactive behavior (e.g., shock sensitivity, detonation wave shape). A detailed nondestructive 3D examination of the microstructure has gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 48 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…In determining which model to use for data analysis, complimentary techniques that can provide real space images of void structures are valuable resources. Several recent x‐ray computed tomography (XCT) studies have found evidence of branched void structures in powders and pressings of TATB and PBX 9502 [28–30], and an SEM investigation of thermally treated PBX 9502 samples revealed complex, interconnected voids throughout the microstructure [31]. From these complementary studies, it is apparent that the voids in TATB and PBX 9502 are not simple spheres and that modeling them as such ignores details of their structure that may be valuable to understanding HE shock properties.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In determining which model to use for data analysis, complimentary techniques that can provide real space images of void structures are valuable resources. Several recent x‐ray computed tomography (XCT) studies have found evidence of branched void structures in powders and pressings of TATB and PBX 9502 [28–30], and an SEM investigation of thermally treated PBX 9502 samples revealed complex, interconnected voids throughout the microstructure [31]. From these complementary studies, it is apparent that the voids in TATB and PBX 9502 are not simple spheres and that modeling them as such ignores details of their structure that may be valuable to understanding HE shock properties.…”
Section: Methodsmentioning
confidence: 99%
“…While both the spherical and ramified models are sensitive to the overall size of a void structure ( R in Figure 2), the ramified model is sensitive to the primary void size ( r in Figure 2) and its correlation within the larger structure. The ramified model provides the level of detail necessary to describe the tortuous void morphology that is evident in recent XCT [28–30] and SEM [31] studies. The ramified model was thus chosen as the better physical representation of the PBX 9502 microstructure, and it was utilized to describe the porosity within baseline and thermally damaged PBX 9502 samples in this work.…”
Section: Methodsmentioning
confidence: 99%
“…It is natural to imagine a void size distribution (VSD) in pressed pieces, but in doing so we tacitly assume that voids are isolated features, like bubbles in a liquid or droplets in a gas. Before [5], such was the picture that the majority of HE workers -ourselves included -tended to have. In retrospect, one understands that it is an assumption of convenience, made for invoking the useful construct of size distributions.…”
Section: Classical Hot Spot Mechanismsmentioning
confidence: 99%
“…Our team recently used dual-energy micro CT to provide a 3D image of bulk PBX material (overall size and shape, cracks and voids), its mesoscale structure (e. g. crystal size, shape, and their distributions) as well as the micro-morphology (e. g. voids or cracks within a single crystal) within both neat-pressed HE and polymer-bonded explosives [5]. Our dual purpose was to guide improved formulations and to provide a starting point for material-aware RFMs.…”
Section: Diagnostic Approachmentioning
confidence: 99%
“…Nitro aromatic compounds (NACs) are widely used in the field of engineering blasting, space applications, explosive forming, and weapon systems. , However, they are highly poisonous and have always been a major safety hazard for human and environmental problems and even threaten national security. Therefore, the scientific community has been attributed to developing detection methods for NACs . At present, the methods for detecting NACs include gas chromatography coupled with mass spectrometry, X-ray imaging and ion mobility spectroscopy, , Raman spectroscopy, and neutron activation analysis and luminescent sensing detection. Among them, the luminescent sensing detection method has received growing attention because of the simple operation and high sensitivity. , O -Phenylenediamine (OPD), m -phenylenediamine (MPD), and p -phenylenediamine (PPD), as a class of isomers of primary aromatic amines, are important raw materials or intermediates in the chemical industry . It is a meaningful and challenging task to develop a simple method to identify them for fields such as in chemistry, biology, and environmental science .…”
Section: Introductionmentioning
confidence: 99%